Comparison between 1D and 2D numerical models of a multi-tubular packed-bed reactor for methanol steam reforming. (29th June 2022) - Zhu, Jimin; Cui, Xiaoti; Araya, Samuel Simon
Abstract: The hydrogen-rich gas produced in-situ by methanol steam reforming (MSR) reactions significantly affects the performance and endurance of the high-temperature polymer electrolyte membrane (HT-PEM) fuel cell stack. A numerical study of MSR reactions over a commercial CuO/ZnO/Al2 O3 catalyst coupling with the heat and mass transfer phenomena in a co-current packed-bed reactor is conducted. The simulation results of a 1D and a 2D pseudo-homogeneous reactor model are compared, which indicates the importance of radial gradients in the catalyst bed. The effects of geometry and operating parameters on the steady-state performance of the reactor are investigated. The simulation results show that the increases in the inlet temperature of burner gas and the tube diameter significantly increase the non-uniformity of radial temperature distributions in reformer tubes. Hot spots are formed near the tube wall in the entrance region. The hot-spot temperature in the catalyst bed rises with the increase in the inlet temperature of burner gas. Moreover, the difference in simulation results between the 1D and 2D models is shown to be primarily influenced by the tube diameter. With a methanol conversion approaching 100% or a relatively small tube diameter, the simplified 1D model can be used instead of the 2D model to estimate the reactor performance. Graphical abstract: Image 1 Highlights: Development of a 2D model for the MSR in a multi-tubular packed-bed reactor. Comparison of simulation results between 1D and 2D reactor models. Prediction of the temperature distribution inside a reactor tube. Studying the effects of geometry and operating conditions on reformer performance. Optimization of operating conditions for integration with a 5 kW HT-PEMFC stack.